Adventures in Flatfrost - Quinn, Jordan (Quinn, Jordan. Kingdom of Wrenly, 2014)
Mischief-makers Prince Lucas, his best friend Clara, and Ruskin the scarlet dragon learn to respect the hard work of others when they are sent to Flatfrost to fetch more ice from the giants who live there.